Analisis Unsur-Unsur Matematika Dalam Novel Buku Panduan Matematika Terapan Karya Triskaidekaman - Nilam Sari Pailokol; Hetriyani Gulo; Aderika Handayani; Nabila Nabila; Nur Indah Sari (Bilangan : Jurnal Ilmiah Matematika, Kebumian dan Angkasa, 2024)
This research aims to determine and describe the mathematical elements in the novel Buku Panduan Matematika Terapan by Triskaideman. This research is a type of qualitative research with a literature study research method. The object of research is the novel Buku Panduan Matematika Terapan by Triskaideman. The results of the analysis of mathematical elements in the Buku Panduan Matematika Terapan novel include the title of the novel, naming of sub-chapters, book content, characters, conflict, and messages in the novel.